2022
DOI: 10.1079/cabireviews202217018
|View full text |Cite
|
Sign up to set email alerts
|

The study of spatial autocorrelation for infectious disease epidemiology decision-making: a systematized literature review

Abstract: In recent years, the global spread of communicable diseases such as Ebola and COVID-19 has stressed the need for clear, geographically targeted, and actionable public health recommendations at appropriate spatial scales. Country-level stakeholders are increasingly utilizing spatial data and spatial decision support systems to optimize resource allocation, and researchers have access to a growing library of spatial data, tools, and software. Application of spatial methods, however, varies widely between researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, due to the diversity of techniques used to identify such clusters (unusual aggregation of epidemics) and hotspots (excess level of epidemics in comparison to a threshold level), their diverse assumptions and the configuration of the data on these results tended to vary within and across studies (19). Spatial analysis is a useful tool for studying the distribution of infectious diseases, which, due to their transmission dynamics, often follow diverse spatial patterns and commonly occur in spatial clusters (42). Four studies reported heterogeneous results, recording the identification of random or clustered patterns that varied across the periods or analytical methods.…”
Section: Spatial Autocorrelation or Spatial Clusteringmentioning
confidence: 99%
“…However, due to the diversity of techniques used to identify such clusters (unusual aggregation of epidemics) and hotspots (excess level of epidemics in comparison to a threshold level), their diverse assumptions and the configuration of the data on these results tended to vary within and across studies (19). Spatial analysis is a useful tool for studying the distribution of infectious diseases, which, due to their transmission dynamics, often follow diverse spatial patterns and commonly occur in spatial clusters (42). Four studies reported heterogeneous results, recording the identification of random or clustered patterns that varied across the periods or analytical methods.…”
Section: Spatial Autocorrelation or Spatial Clusteringmentioning
confidence: 99%